Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1177/0363546515626199
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of the Remplissage Procedure and Its Effects on Return to Sports

Abstract: The redislocation rate after remplissage was 11.8% at an average of 5 years, with 95.5% of patients returning to full sports at an average of 7 months. For throwing sports, 65.5% of patients complained of decreased range of motion during throwing. The results should be considered preoperatively in candidates for remplissage who are engaged in throwing sports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(58 citation statements)
references
References 42 publications
4
45
0
4
Order By: Relevance
“…Three-dimensional CT reconstruction is currently considered the gold standard for the evaluation of bone loss, 10,53 although MRI has also demonstrated consistent correlation with CT in many studies. 27,34 Several techniques for classifying attritional glenoid bone loss 6,7 and Hill-Sachs lesions 51 have been described, and more than 20% to 25% anterior-inferior glenoid loss has been suggested as a critical threshold for increased failure with isolated labral repair. 13,33,50 More recently, the lower limit of this bone loss has been questioned, with so-called “subcritical” bone loss of 13.5% leading to suboptimal outcomes with arthroscopic treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three-dimensional CT reconstruction is currently considered the gold standard for the evaluation of bone loss, 10,53 although MRI has also demonstrated consistent correlation with CT in many studies. 27,34 Several techniques for classifying attritional glenoid bone loss 6,7 and Hill-Sachs lesions 51 have been described, and more than 20% to 25% anterior-inferior glenoid loss has been suggested as a critical threshold for increased failure with isolated labral repair. 13,33,50 More recently, the lower limit of this bone loss has been questioned, with so-called “subcritical” bone loss of 13.5% leading to suboptimal outcomes with arthroscopic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…While the glenoid has traditionally been the area of focus, characteristics of the Hill-Sachs lesion have recently received increased attention. 15,27 Though often ill-defined, clinically significant humeral-based defects may be effectively treated with remplissage as a nonanatomic complement to arthroscopic anterior stabilization (Figure 2). A randomized clinical trial comparing remplissage and Bankart reconstruction to Bankart alone demonstrated no recurrences in the combined group compared with 20% recurrence in the isolated group.…”
Section: Managementmentioning
confidence: 99%
“…7,14,17 Even with small losses of only 2° to 8°, 3,4,19 the effects may have a greater impact in overhead athletes. 9 One explanation for external rotation loss may be due to overmedialization of suture placement. Elkinson et al 7 found placing anchors 1 cm more medial to the desired position in the posterior capsule significantly increased joint stiffness and reduced range of motion.…”
Section: Discussionmentioning
confidence: 99%
“…Garcia et al reported an average ASES score post-remplissage of 89.3 at an average follow-up time of 60.7 months. 10 Merolla et al used the same procedure and reported a mean Constant-Murley score of an increase from 62.9 + 7.1 preoperatively to 90 + 5.2 at a median follow-up of 39.5 months. 11 Similarly, Wolf and Arianjam reported a postoperative mean Constant score of 92 + 10 at an average follow-up of 58 months.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] However, many patients also experience limitation in external and internal rotation of the joint following this procedure. 6,[9][10][11] Garcia et al reported that 66.5% of patients experienced a reduced range of motion in throwing after the remplissage procedure. 10 This limitation in shoulder range of motion has also been shown in cadaveric studies.…”
Section: Introductionmentioning
confidence: 99%